Implementasi Aplikasi SIMPELDESA Sebagai Inovasi Penyelenggaraan Layanan Publik Oleh Pemerintah Desa Sumberjaya Kecamatan Cihaurbeuti Kabupaten Ciamis - Nesta Sintawati; Aan Anwar Sihabudin; Abdul Mutholib (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to find out the causes of the non-optimal implementation of the SIMPELDESA application as an innovation in the implementation of public services by the government of Sumberjaya Village, Cihaurbeuti District, Ciamis Regency. This study uses a qualitative research design. The primary data source was obtained through observation and interviews with seven informants. Secondary data is obtained from documents, laws, and journals that have relevance to the topic of research. Data collection techniques are carried out through observation, interviews and documentation. The data analysis technique uses triangulation techniques consisting of data reduction, data presentation and conclusion drawn. The results of the study show that the implementation of SIMPELDESA as a public service innovation in Sumberjaya village is not optimal. This is evidenced by two indicators that are not optimal, namely Complexity, and Compability. The obstacles that occur are the lack of knowledge, understanding, internet infrastructure, socialization, and education to the community that has not reached the community completely. Efforts to overcome these obstacles are conducting training for village officials, community socialization, hybrid-based services, strengthening digital literacy, improving infrastructure, and developing the SIMPELDESA application to be more efficient, transparent, and accountable.